First-year students at an open distance and e-learning institution: Perceptions, expectations and challenges associated with academic writing feedback - Maphoto, Kgabo (Journal for Language Teaching, 2022)
While constructive feedback is known to be the most valuable teaching tool in various teaching contexts., the findings revealed that the feedback students receive is below the standard that they expect, is confusing and inadequate for addressing most of the sociocultural challenges they encounter. The objective of this study was to examine perceptions, expectations and challenges associated with the feedback that first-year English studies students receive in an Academic Writing module (ENG100) at an open distance and e-learning institution in South Africa. First-year students who speak English as an additional language experience difficulty in understanding the feedback they receive in their academic writing tasks. The study followed a qualitative approach that obtained data from participants through online open-ended evaluation questions. Random sampling was utilised to select a sample size from a population of approximately 16 000 students. Therefore, this paper, proposes that academic writing modules should view writing as a social skill and not as a subject.